PERLINDUNGAN HUKUM BAGI PEMILIK TANAH ATAS PEMBATALAN SERTIFIKAT OLEH PENGADILAN TATA USAHA NEGARA (PTUN) YANG BERASAL DARI TANAH ADAT TANPA ADANYA PELEPASAN HAK. - Hardhini, Euis; Franciska, Wira; Halim, Anriz Nazaruddin (LPPM Institut Pendidikan Nusantara Global, 2024)
Landowners face serious challenges when their land titles are annulled by the Administrative Court (PTUN) rooted in customary lands. In the course of this law, the main focus is the right of ownership, the existence of landowners, and the influence of customary land. Without a clear waiver of rights, this legal complexity calls into question the existence and right of ownership of the landowner. In this context, a legal and ethical obligation arises to protect the rights of landowners, especially those from indigenous lands, answer the call of legal protection, and ensure justice and equality before the law. The method used in this research is normative juridical legal research, which was carried out as an effort to obtain the necessary data regarding the problem. The data used is primary data as supporting legal material for secondary data. Data analysis was carried out using qualitative analysis methods. The result of this study is that landowners are at risk of losing legal certainty and protection if their certificates are canceled by the Administrative Court, especially related to customary land without a clear waiver of rights. The cancellation requires the revocation of the certificate, resulting in the inability of the certificate holder to physically control the land and cause harm to all parties, according to the theory of the consequences of Soeroso law and the legal protection of landowners related to the cancellation of certificates by the court from customary land without waiver involving the settlement of land disputes. Generally, land disputes can be resolved through customary deliberations, led by Adat Para-Para, or through a court in the settlement of land cases.